2011
DOI: 10.1155/2011/685249
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Cardiopulmonary Resuscitation Training to Chinese Immigrants with Limited English Proficiency

Abstract: Cardiopulmonary resuscitation (CPR) is an effective intervention for prehospital cardiac arrest. Despite all available training opportunities for CPR, disparities exist in participation in CPR training, CPR knowledge, and receipt of bystander CPR for certain ethnic groups. We conducted five focus groups with Chinese immigrants who self-reported limited English proficiency (LEP). A bilingual facilitator conducted all the sessions. All discussions were taped, recorded, translated, and transcribed. Transcripts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…A further two studies documented CPR knowledge and training in Chinese communities with limited English proficiency (LEP) in the USA. One study conducted by Yip et al ( 2011 ) in Seattle, Washington, noted that CPR training was predominantly offered in English and was less available to communities with LEP. As the training is mostly conducted in English, there was limited awareness of CPR knowledge in the Chinese community, and very few community members had actually received instruction (Yip et al , 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further two studies documented CPR knowledge and training in Chinese communities with limited English proficiency (LEP) in the USA. One study conducted by Yip et al ( 2011 ) in Seattle, Washington, noted that CPR training was predominantly offered in English and was less available to communities with LEP. As the training is mostly conducted in English, there was limited awareness of CPR knowledge in the Chinese community, and very few community members had actually received instruction (Yip et al , 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study conducted by Yip et al ( 2011 ) in Seattle, Washington, noted that CPR training was predominantly offered in English and was less available to communities with LEP. As the training is mostly conducted in English, there was limited awareness of CPR knowledge in the Chinese community, and very few community members had actually received instruction (Yip et al , 2011 ). The study’s findings identified the use of local media to advertise programmes, to increase community involvement and to equip community members with skills to increase CPR bystander uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers of limited opportunities to train — as well as reluctance to respond due to poor knowledge, fear of causing harm, and fear of legal consequences — have been identified in several other studies 4–7 34–38. Most other studies exploring CPR knowledge and willingness among migrant, minority or disadvantaged population groups are from the USA, where a different context for migrant groups and experiences are reported 13 39–42. A qualitative investigation in Latino neighbourhoods in Denver, Colorado, found immigration status, language, racism and fear of touching someone they did not know, or touching a female, were among the cultural barriers identified that could prevent someone from performing CPR 34.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified legal implications, concerns of causing harm, the home country’s cultural norms and attention to safety, first-aid, and emergency response contributed to attitudes towards BLS 43–45. Studies among Chinese immigrants living in the USA identified that CPR knowledge and training were poor, and the possibility of liability was one of the barriers to learning CPR 13. Country-specific laws and the overall social environment may influence willingness, as noted in previous research conducted in China and India with poor protection laws35 46 and among minority groups in nations where protective ‘good Samaritan laws’ have existed for a long time 34 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation